How Behavioral Factors Shape Intentions Toward Cash Waqf Linked Sukuk in Indonesia? - Andni, Riyan; Aris, Nur; Widodo, Syukri Fathudin Achmad; Anam, Ahmad Muzakkil (Share: Jurnal Ekonomi dan Keuangan Islam, 2025)
Cash Waqf Linked Sukuk (CWLS) represents an innovative social investment instrument in Indonesia, combining cash waqf (Islamic endowment) with government sukuk (Sharia-compliant bonds). Despite its significant role in funding education, healthcare, and economic development, the substantial potential of CWLS remains underutilized due to a disparity between its projected benefits and the limited participation of potential investors. The study aims to predict the intention of Islamic banking customers to engage in cash waqf through State Sukuk or CWLS in West Java. It employs the Theory of Planned Behavior (TPB) to investigate the behavioral intentions of Islamic banking customers in West Java, Indonesia, toward adopting CWLS. Using a quantitative approach, data were collected from 119 respondents who are active customers of Islamic banks. The findings reveal that attitude toward behavior and subjective norms do not significantly influence behavioral intention, whereas perceived behavioral control (PBC) emerges as a critical predictor of intention to participate in CWLS. Among demographic variables, only age moderates the relationship between attitude toward behavior and behavioral intention. The study identifies low public awareness, limited financial literacy, and mistrust in CWLS mechanisms as key barriers. To bridge this gap, stakeholders must prioritize widespread socialization campaigns, particularly targeting productive-age demographics, to enhance trust and literacy. Strategic promotion of CWLS’s dual benefits—social impact and financial returns—is recommended to accelerate investor participation and maximize its socioeconomic potential.========================================================================================================ABSTRAK - Bagaimana Faktor Perilaku Membentuk Niat Investasi dalam Cash Waqf Linked Sukuk di Indonesia? Cash Waqf Linked Sukuk (CWLS) merupakan instrumen investasi sosial inovatif di Indonesia yang menggabungkan wakaf uang dengan sukuk negara (surat berharga syariah). Meskipun berperan penting dalam mendanai sektor pendidikan, kesehatan, dan pembangunan ekonomi, terdapat kesenjangan antara potensi yang ditimbulkan atas manfaat CWLS dan calon investor potensial. Penelitian ini bertujuan untuk memprediksi niat nasabah perbankan syariah dalam mewakafkan uang melalui sukuk negara atau CWLS di Jawa Barat. Penelitian ini menggunakan ‘Theory of Planned Behavior’ (TPB) untuk menganalisis niat perilaku calon investor dalam menggunakan CWLS dari perspektif nasabah Perbankan syariah. Metode kuantitatif diterapkan dengan melibatkan 119 responden nasabah bank syariah. Hasil penelitian menunjukkan bahwa ‘attitude toward behavior’ (sikap) dan ‘subjective norms’ (norma subjektif) tidak berpengaruh signifikan terhadap ‘behavioral intention’ (niat berperilaku), sementara ‘perceived behavioral control’ (PBC) menjadi prediktor utama ‘behavioral intention’ atau niat berpartisipasi dalam CWLS. Dari variabel demografi, hanya usia yang memoderasi hubungan antara sikap dan niat berperilaku. Rendahnya kesadaran masyarakat, literasi keuangan terbatas, dan ketidakpercayaan terhadap mekanisme CWLS diidentifikasi sebagai hambatan utama. Untuk mengatasi hal ini, pemangku kepentingan perlu meningkatkan sosialisasi, khususnya kepada kelompok usia produktif, guna memperkuat kepercayaan dan pemahaman masyarakat. Promosi strategis mengenai manfaat ganda CWLS—dampak sosial dan keuntungan finansial—direkomendasikan untuk memperluas partisipasi investor dan memaksimalkan potensi sosial-ekonomi instrumen ini.